2016
DOI: 10.3109/14992027.2015.1120892
|View full text |Cite
|
Sign up to set email alerts
|

Predicting three-month and 12-month post-fitting real-world hearing-aid outcome using pre-fitting acceptable noise level (ANL)

Abstract: Objective Determine the extent to which pre-fitting acceptable noise level (ANL), with or without other predictors such as hearing aid experience, can predict real-world hearing aid outcomes at 3 and 12 months post-fitting. Design ANLs were measured before hearing aid fitting. Post-fitting outcome was assessed using the International Outcome Inventory for Hearing Aids (IOI-HA) and a hearing aid use questionnaire. Models that predicted outcomes (successful vs. unsuccessful) were built using logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
12
2
2
Order By: Relevance
“… Nabelek, Freyaldenhoven, Tampas, Burchfiel, and Muenchen (2006) showed that unaided ANLs had an 85% accuracy rate at predicting successful hearing aid use in individuals who had worn hearing aids for 3 months to 3 years. Wu, Ho, Hsiao, Brummet, and Chipara (2016) measured ANL in 132 adults before hearing aid fitting and reported 55% to 68% accuracy at predicting real-word hearing aid outcomes as evaluated by the International Outcome Inventory for Hearing Aids (IOI-HA; Cox & Alexander, 2002 ). These studies hypothesized that, if NR algorithms could increase noise tolerance, they would turn individuals with high ANLs into more successful hearing device users.…”
Section: Introductionmentioning
confidence: 99%
“… Nabelek, Freyaldenhoven, Tampas, Burchfiel, and Muenchen (2006) showed that unaided ANLs had an 85% accuracy rate at predicting successful hearing aid use in individuals who had worn hearing aids for 3 months to 3 years. Wu, Ho, Hsiao, Brummet, and Chipara (2016) measured ANL in 132 adults before hearing aid fitting and reported 55% to 68% accuracy at predicting real-word hearing aid outcomes as evaluated by the International Outcome Inventory for Hearing Aids (IOI-HA; Cox & Alexander, 2002 ). These studies hypothesized that, if NR algorithms could increase noise tolerance, they would turn individuals with high ANLs into more successful hearing device users.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptable noise level (ANL) test was developed to quantify the critical amount of background noise that subjects could accept while listening to speech [16]. ANL is defined as the lowest signal-to-noise ratio (SNR) that a subject could accept when the target speech was presented at the most comfortable listening level (MCL) [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…ANL is defined as the lowest signal-to-noise ratio (SNR) that a subject could accept when the target speech was presented at the most comfortable listening level (MCL) [6, 7]. ANL is derived by subtracting the background noise level (BNL) that the subject can accept from the MCL.…”
Section: Introductionmentioning
confidence: 99%
“…AI has also been used to support clinical diagnoses and treatments, decision-making, the Table 4. Continued prediction of prognoses [98][99][100]125,126], disease profiling, the construction of mass spectral databases [43,[127][128][129], the identification or prediction of disease progress [101,105,[107][108][109][110]130], and the confirmation of diagnoses and the utility of treatments [102][103][104]112,131]. Although many algorithms have been applied, some are not consistently reliable, and certain challenges remain.…”
Section: Discussionmentioning
confidence: 99%
“…In medical device-based analyses, AI is used to evaluate tissue and blood test results, as well as the outcomes of otorhinolaryngology-specific tests (e.g., polysomnography) [ 72 , 73 , 122 ] and audiometry [ 123 , 124 ]. AI has also been used to support clinical diagnoses and treatments, decision-making, the prediction of prognoses [ 98 - 100 , 125 , 126 ], disease profiling, the construction of mass spectral databases [ 43 , 127 - 129 ], the identification or prediction of disease progress [ 101 , 105 , 107 - 110 , 130 ], and the confirmation of diagnoses and the utility of treatments [ 102 - 104 , 112 , 131 ].…”
Section: Discussionmentioning
confidence: 99%